Kewenangan dan Tanggung Jawab Notaris Terhadap Akta Wasiat yang di Buat Dihadapannya di Kota Padang - Salma Hayaturrahmi; Azmi Fendri; M Hasbi (UNES Law Review, 2023)
A will is a ideed that contains a person's statement about what he wants to happen after he dies, and which can be revoked by him. Notary as a public official is given by laws and regulations the authority to make all agreements and deeds as well as what is desired by those concerned. One of the powers of a notary is to make a deed relating to a will, this is in accordance with the provisions in Article 16 paragraph (1) letter j and k of the Notary Office Law. This study proposes the formulation of the problem, namely: 1 What is the authority of a notary regarding a will made before him in the city of Padang? 2. What are the notary's obligations regarding the will made before him in the city of Padang? 3. What is the form of the Notary's responsibility for the will made before him in the icity of Padang? This research uses a juridical-empirical approach. The results of the research that has been carried out are: 1. The notary's authority over a will made before him in the city of Padang, namely the authority granted by law to a notary is to make a deed related to a will as mandated in UUJN which is related to Article 16 paragraph (1) letter i which reads: "make a list of ideeds relating to the will according to the order in which the deed was drawn up every month". A will includes a deed drawn up before a notary. A will made directly before a notary is a public will or open will. In this case, the party who wants to make a will comes personally before the notary and states his will. Furthermore, the notary makes the will desired by the person facing it. 2. The notary's obligation to the testamentary deed drawn up before him in the city of Padang is to notify, report and register all wills he makes to the Central List of Probates (DPW) and the Probate Court (BHP) both open wills (openbaar itestament), written wills (olographis testament) as well as a closed or secret testament. 3. Responsibilities of the Notary regarding the will made before him in the City of Padang, include the following: a.) Moral responsibility. b.) Ethical responsibility. c.) Legal responsibility (formal and material).